2017
DOI: 10.1007/s40653-017-0156-x
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of the Relationship between Experiences with Sibling Abuse and Peer Bullying: a Pilot Study

Abstract: This paper uses peer reviewed research and a comprehensive literature review to highlight some of connections and similarities between experience with sibling abuse and experience with peer bullying. Specifically, an altered version of the Conflict Tactics Scale (Straus Journal of Marriage and the Family, 41, 75-88, 1979) was used to empirically explore the potential relationship between experience with peer bullying as a survivor or perpetrator, and experience with sibling abuse as a survivor or perpetrator. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…However, family competence had a negative correlation with bullying. These findings are in keeping with those found by studies conducted in other contexts (Ciucci & Baroncelli, 2014; Dadds et al, 2013; Hawes et al, 2014; Morrill et al, 2018; Nwafor et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, family competence had a negative correlation with bullying. These findings are in keeping with those found by studies conducted in other contexts (Ciucci & Baroncelli, 2014; Dadds et al, 2013; Hawes et al, 2014; Morrill et al, 2018; Nwafor et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, studies reported that bullies are more likely to perceive their family as less cohesive and as less concerned about each other’s problems and needs (Flouri & Buchanan, 2003; Steven & Joyce, 2002). Furthermore, studies have shown that those who bully their siblings at home are more likely to bully their peers (Morrill, Bachman, Polisuk, Kostelyk, & Wilson, 2018; Tippett & Wolke, 2015; Wolke & Skew, 2011). Also, parenting behaviour such as abuse, neglect, and maladaptive parenting are associated with bullying behaviour, while positive parenting behaviour including good parent–child communication and warm and affectionate relationship are protective against bullying behaviour (Baldry, 2003; Flouri & Buchanan, 2003; Lereya, Samara, & Wolke, 2013; Spriggs, Iannotti, Nansel, & Haynie, 2007).…”
Section: Family Competence and Bullyingmentioning
confidence: 99%
“…Moreover, there is some research indicating that peer and sibling victimization often co-occur [17][18][19]. Approximately 15% of youth experience both peer and sibling victimization, with sibling victimization being more common during childhood (e.g., school-aged) and typically preceding peer victimization [20][21][22].…”
Section: Victimization and Internalizing Symptomsmentioning
confidence: 99%
“…While areas of familial violence such as parent-child abuse, intimate partner violence, and elderly abuse have gained much attention over the past several decades, relatively little consideration has been focused on sibling abuse of other children. The lack of research is surprising given that studies suggest sibling abuse is actually the most common form of family violence (Morrill et al 2018;Straus 2001).…”
Section: Historical Contextmentioning
confidence: 99%